Mechanical And Tribological Properties Of FFF 3D-Printed Polymers: A Brief Review - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli; Tamaldin, Noreffendy; Amiruddin, Hilmi; Ramli, Faiz Redza; Mohamad Norani, Mohamad Nordin (Malaysian Tribology Society (Mytribos), 2021)
In fused filament fabrication (FFF); the process of 3D printing using polymer-based materials; specialised and functional parts are designed and manufactured for use in engineering and medical industries. Recognizing the impact on the mechanical and tribological behaviour of different processing parameters, composite materials, internal geometries, and lattices will allow a better understanding of the characteristics of FFF end-products. However, obtaining this information proves to be complicated. The review of current literature and research related to the use in real-life applications is therefore essential, as this will not only help to identify valuable characteristics, vital processing parameters, and limitations, but will also help to understand the results of these studies. As such, a systematic and classification-based literature review was performed on the mechanical and tribological properties of 3D-printed polymers.